Pelaksanaan Pilkada di Pondok Pesantren Musthafawiyah purba Baru pada pemilihan Gubernur Tahun 2018 - Rizki Sufi Amelia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study examines the Implementation of the Pilkada at the New Musthafawiyah Islamic Boarding School in the 2018 Gubernatorial Election. This research is a field research using a normative juridical approach, the primary data source is the Chairperson of the Election Commission of Mandailing Natal Regency, the Chairperson of the Purba Baru Islamic Boarding School Foundation, the Chairperson of the Muadallah Aliyah Islamic Boarding School. New Purba Musthafawiyah, and New Ancient Musthafawiyah Islamic Boarding School Students. secondary data is data that includes documents related to this research, data collection techniques with observation, interviews and documentation, and qualitative descriptive analysis. The results of this study prove that the Implementation of Pilkada at the New Musthafawiyah Islamic Boarding School in the 2018 Governor Election, based on Article 61 paragraph (1), (2), (3), and (4) Law Number 10 of 2016 concerning the Election of Governors in terms of Fiqh The General Election Commission's policy in making decisions about student suffrage is not based on general principles. benefit principle. The inhibiting factors for the students of the Musthafawiyah Purba Baru Islamic Boarding School in exercising their voting rights were, among others, internal factors, the difficulty of managing files or certificates of moving to vote from the original TPS to the destination TPS. where they choose.